Self-consciousness and Absolute - Ciancio, Claudio (Religija ir kultūra, 2013)
The Philosophies of Mind do not take into account the qualitative differences existing between the various representative contents of human consciousness. Yet, the specificity which differentiates it from animal consciousness lies in the fact that it also represents the absolute and freedom. Since these notions represent absolute otherness, they exceed, as such, the capacity of consciousness. The collision with this excess returns consciousness to itself thus setting it free. In this way, it becomes the image of the absolute.